PENGARUH GREEN MARKETING DAN MARKETING MIX TERHADAP CUSTOMER PREFERENCE DAN DAMPAKNYA TERHADAP KEPUTUSAN PEMBELIAN (Studi pada Mahasiswa S2 Konsumen Aqua-Danone, Fakultas Ilmu Administrasi Universitas Brawijaya. Malang) - Riswati, Any; Suharyono, Suharyono; Kumadji, Srikandi (Profit: Jurnal Adminsitrasi Bisnis, 2015)
Green marketing is the concept of green marketing that is friendly to nature and environmental sustainability, green marketing is defined as a management process responsible for identifying, anticipating and satisfying the needs of consumers is profitable and sustainable (Peattie, 1992). Aqua Danone uses green marketing strategy as environmentally friendly marketing strategy shaft successful, because aqua have an environmental policy "Ground Water Policy" in managing the environment. Supported by the marketing mix strategy as the best communication tool for consumers in determining the choice of eco-friendly products before deciding to buy and consume products that benefit consumers and the environment. This study uses path analysis (path analysis) along with hypothesis testing to determine significant influence on the variables that are already defined. Population taken from S2 FIA UB student consumer Danone Aqua, with a sample of 75 people with the questionnaire data collection techniques shoot one study. The results of green marketing on customer  preference  significantly,  green  marketing  is  not  a  significant  influence  on purchasing decisions, marketing mix insignificant effect on customer preferences, marketing mix significantly influence purchase decisions, and customer preferences significantly influence purchasing decisions. The study was limited to one-shoot-study used data. Future research is expected to use this type of qualitative research in order to know in detail the impact of products on the environment in the long term.